2008
DOI: 10.1080/13506120701815456
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever gene mutations in the Southeastern region of Turkey and their phenotypical features

Abstract: Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by recurrent inflammatory attacks of serosal membranes. Several studies have focused on the differences between frequency of the mutations and their phenotypical manifestations. The aim of this study was to evaluate whether or not this phenotypical variation is associated with the existence of particular mutations. Twelve MEFV (Mediterranean fever) gene mutations were investigated in 119 patients suffering from FMF. Heterozygote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
3
28
2
2
Order By: Relevance
“…1 Se ve ral stu di es from dif fe rent coun tri es as well as dif fe rent re gi ons of Tur key ha ve emp ha si zed that M694V ho mozy go us ge noty pe have a mo re se ve re form of di se a se ma ni fes ted by an ear li er age of on set, hig her fre qu ency of at tacks, hig her pre va len ce of art hri tis and ple u risy, hig her fre qu ency of amy lo i do sis and hig her se ve rity scores compared to the ot her ge noty pes. 2,11,[20][21][22][23][24][25] On the con trary, so me stu di es sho wed that the pre sen ce of M694V mu ta ti on was not fo und to be as so ci a ted with a se ve re form of the di se a se or the de ve lopment of amy lo i do sis. 2,9,11 Re cently, in a lar ge co hort study from the Ae ge an re gi on of Tur key, the M694V ho mozy go us mu ta ti on was fo und most frequ ently in a de fi ni ti ve FMF gro up, ba sed on TelHas ho mer cri te ri a.…”
Section: Discussionmentioning
confidence: 99%
“…1 Se ve ral stu di es from dif fe rent coun tri es as well as dif fe rent re gi ons of Tur key ha ve emp ha si zed that M694V ho mozy go us ge noty pe have a mo re se ve re form of di se a se ma ni fes ted by an ear li er age of on set, hig her fre qu ency of at tacks, hig her pre va len ce of art hri tis and ple u risy, hig her fre qu ency of amy lo i do sis and hig her se ve rity scores compared to the ot her ge noty pes. 2,11,[20][21][22][23][24][25] On the con trary, so me stu di es sho wed that the pre sen ce of M694V mu ta ti on was not fo und to be as so ci a ted with a se ve re form of the di se a se or the de ve lopment of amy lo i do sis. 2,9,11 Re cently, in a lar ge co hort study from the Ae ge an re gi on of Tur key, the M694V ho mozy go us mu ta ti on was fo und most frequ ently in a de fi ni ti ve FMF gro up, ba sed on TelHas ho mer cri te ri a.…”
Section: Discussionmentioning
confidence: 99%
“…Five founding mutations M694V, V726A, M680I, M694I (in exon 10), and E148Q (in exon 2) are the most common MEFV mutations (Sarrauste De Menthière C, 2003;Milhavet et al, 2008). Several reports have shown that the M964V mutation is associated with severe disease featuring early onset, high frequency of attacks, the need for the high doses of colchicine and high frequency of amyloidosis in untreated patients (Saatçi et al, 1997;Mattitt et al, 2006;Düşünsel et al, 2008;Paşa et al, 2008;Jarjour, 2010). The syndrome also features high levels of erythrocyte sedimentation rate, C-reactive protein and serum amyloid A, but case-specific consensus on phenotype and genotype in FMF patients has not been reached (Aldea et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In our study group, the most frequent MEFV mutation was also M694V, and based on this result, we suggested that the distribution of MEFV gene mutations does not differ greatly between the different geographic areas of Turkey.…”
Section: Discussionmentioning
confidence: 84%
“…14 (Black Sea region/Turkey), Paa et al 13 (Southeastern region/Turkey) and Solak et al 4 (Aegean region/Turkey) reported that amyloidosis was more frequent in adult patients with the M694V/M694V genotype. Gürkan et al 5 (Trakya region/Turkey) also detected no amyloidosis in two adult patients with the M694V/ M694V genotype.…”
Section: Yigit Et Almentioning
confidence: 99%